Classification of Readers Reception of Surah Al-Waqiah in Mujahadah Waqiah According to Hall’s Reception Theory - Ulya, Ulya; Muamalah, Sholihatun (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
Surah Al-Waqiah is believed to contain many virtues, among others, it will bring abundant sustenance and avoid poverty and destitution for its readers.  Therefore, many Muslims interact directly with it. At Al-Mawaddah Islamic Boarding School in Kudus, this interaction is embodied in the tradition named with Mujahadah Waqiah. The article aims to find out the classification of reception for residents of Al-Mawaddah as readers Surah Al-Waqiah in Mujahadah Waqiah. Using a descriptive qualitative approach, the research draws on field data collected through semi-structured interviews, non-participant observation, and documentation from caregivers, teachers, students, and community members involved in the tradition. The collected data is interpreted based on Stuart Hall's reception theory.  Based on the theory, there are two classifications the residents of Al-Mawaddah receipt Surah Al-Waqiah in Mujahadah Waqiah. Some are the dominant readers, but most of them are negotiation readers. This latest finding further confirms the theory that readers are not passive, but active. Interest factors, individual experiences, and social relations play a very important role in the reception process of the residents of the Al-Mawaddah Islamic Boarding Scholl in Kudus towards Surah Al-Waqiah.Surah Al-Waqiah diyakini mengandung banyak keutamaan, antara lain, akan mendatangkan rezeki yang melimpah dan terhindar dari kefakiran dan kemiskinan bagi pembacanya. Oleh karenanya banyak orang Islam yang berinteraksi langsung dengannya. Interaksi warga Pesantren Al-Mawaddah di Kudus dengan Surah Al-Waqiah diimplementasikan dalam tradisi Mujahadah Waqiah. Artikel bertujuan mengetahui klasifikasi resepsi warga Pesantren Al-Mawaddah Kudus sebagai pembaca Surah Al-Waqiah dalam Mujahadah Waqiah.  Artikel ini merupakan hasil penelitian lapangan dengan pendekatan deskriptif kualitatif. Sumber datanya berasal dari para pengasuh, guru, santri, juga masyarakat sekitar yang terlibat dalam tradisi tersebut. Pengumpulan data dilakukan melalui wawancara semi terstruktur, observasi non-partisipatoris, dokumentasi. Data yang terkumpul diinterpretasikan berdasarkan teori resepsi Stuart Hall. Berdasarkan teori Hall, ditemukan 2 (dua) klasifikasi warga pesantren Al-Mawaddah dalam meresepsi Surah Al-Waqiah pada Mujahadah Waqiah. Sebagian sebagai pembaca dominan, namun sebagian besar mereka menjadi pembaca negosiasi. Temuan terakhir ini semakin menegaskan teori bahwa pembaca bukankah pihak yang pasif, tetapi aktif. Faktor kepentingan, pengalaman individual, relasi sosial sangat berperan dalam proses resepsi warga Pesantren al-Mawaddah Kudus terhadap Surah  Al-Waqiah.